The Cost Effectiveness of Hand Held Ultrasound Scanning for Abdominal Aortic Aneurysm in Older Males with a History of Smoking - Denver Phiri; Peter J. Mallow; John A. Rizzo (Journal of Health Economics and Outcomes Research)
**Objective:** Abdominal aortic aneurysm (AAA) is a serious illness occurring in 1 of 20 older men. Guidelines emphasize the role of ultrasound scanning for patients at risk of AAA, yet the cost effectiveness of such scanning remains uncertain. New pocket mobile echocardiography (PME) devices may enhance the cost effectiveness of such scanning due to its low cost, ability to be used in primary care settings, and high degree of accuracy. This study performs cost utility analyses (CUAs) comparing opportunistic scanning for AAA using a PME to usual care for a hypothetical cohort of 10,000 male smokers age 65+.